2017
DOI: 10.1128/jvi.00011-17
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox Virus Host Factor Screen Using Haploid Cells Identifies Essential Role of GARP Complex in Extracellular Virus Formation

Abstract: (MPXV) is a human pathogen that is a member of the genus, which includes and (the causative agent of smallpox). Human monkeypox is considered an emerging zoonotic infectious disease. To identify host factors required for MPXV infection, we performed a genome-wide insertional mutagenesis screen in human haploid cells. The screen revealed several candidate genes, including those involved in Golgi trafficking, glycosaminoglycan biosynthesis, and glycosylphosphatidylinositol (GPI)-anchor biosynthesis. We validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 51 publications
4
65
0
1
Order By: Relevance
“…We hypothesized that this alteration in surface protein glycosylation would decrease the enrichment and overabundance of hits related to HS protein glycosylation and nonspecific virus binding. Nevertheless, consistent with a wide range of virus-selected genome-wide loss of function screens (Hoffmann et al, 2017;Jae et al, 2014;Realegeno et al, 2017;Riblett et al, 2016), we identified host factors involved in heparan sulfate biosynthesis.…”
Section: Genome-wide Crispr-cas9 Screens For Zika and Yellow Fever VIsupporting
confidence: 74%
“…We hypothesized that this alteration in surface protein glycosylation would decrease the enrichment and overabundance of hits related to HS protein glycosylation and nonspecific virus binding. Nevertheless, consistent with a wide range of virus-selected genome-wide loss of function screens (Hoffmann et al, 2017;Jae et al, 2014;Realegeno et al, 2017;Riblett et al, 2016), we identified host factors involved in heparan sulfate biosynthesis.…”
Section: Genome-wide Crispr-cas9 Screens For Zika and Yellow Fever VIsupporting
confidence: 74%
“…The vaccine against smallpox in humans has been shown to be 85% effective against monkeypox (21) but issues with vaccine safety and relatively small numbers of cases have not justified vaccination. Further, monkeypox is occurring in areas which struggle to maintain adequate vaccine coverage levels for routine vaccinations against measles and polio, which remain a higher priority (41). The global increase in monkeypox should be a cause of concern.…”
Section: Critical Analysismentioning
confidence: 99%
“…While several viruses (Simian virus 40, papillomavirus, and influenza) rely on retrograde transport for entry into a cell, OPXVs require retrograde transport for EV membrane wrapping, and consequently viral egress (Spooner et al, 2006;Harrison et al, 2016;Sivan et al, 2016). We and others have previously demonstrated that impeding the retrograde pathway by targeting the Golgi-associated retrograde protein complex can greatly reduce EV yield with minimal impact on MV formation in VACV and MPXV (Harrison et al, 2016;Realegeno et al, 2017). Treatment with small molecule inhibitors of the retrograde pathway such as Retro-1 and Retro-2 significantly decreased EV formation in vitro by preventing the trafficking of the viral protein F13, which is required for membrane wrapping (Harrison et al, 2016;Sivan et al, 2016).…”
Section: Introductionmentioning
confidence: 96%